2015
DOI: 10.1016/j.respol.2014.10.006
|View full text |Cite
|
Sign up to set email alerts
|

Regional disadvantage? Employee non-compete agreements and brain drain

Abstract: JEL classification: O30 O38 R10 R12 Keywords:Non-compete agreements Labor mobility Regional economics a b s t r a c t A growing body of research has documented the local impact of employee non-compete agreements, but their effect on interstate migration patterns remains unexplored. Exploiting an inadvertent policy reversal in Michigan as a natural experiment, we show that non-compete agreements are responsible for a "brain drain" of knowledge workers out of states that enforce such contracts to states where th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
105
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 139 publications
(111 citation statements)
references
References 46 publications
5
105
0
1
Order By: Relevance
“…It is clear that policies to promote national, state, and regional levels could have positive or negative influences on entrepreneurship. To illustrate, it is now widely accepted that the lack of enforceability of noncompete agreements in states such as California has had a positive impact on entrepreneurship (Marx, Singh, & Fleming, 2015).…”
Section: Regulations and Policy-related Factorsmentioning
confidence: 99%
“…It is clear that policies to promote national, state, and regional levels could have positive or negative influences on entrepreneurship. To illustrate, it is now widely accepted that the lack of enforceability of noncompete agreements in states such as California has had a positive impact on entrepreneurship (Marx, Singh, & Fleming, 2015).…”
Section: Regulations and Policy-related Factorsmentioning
confidence: 99%
“…Marx, Strumsky, and Fleming found that Michigan's policy changes resulted in a brain drain from Michigan ( , Marx et al 2015. Belenzon & Schankerman (2013) find that a state's enforcement of non-compete clauses decreases instate knowledge spillovers, as well as increasing knowledge workers' out-migration.…”
Section: Learning In Networkmentioning
confidence: 99%
“…As we study mobile employees, it is important to highlight that though NCCs have a dampening effect on labor mobility (Marx et al, 2009;Png & Samila, 2013), they do not prevent mobility on a large scale -which would restrict the generalizability of our findings. In Prior literature argued that a restriction of labor mobility negatively affects the economic development of geographic regions due to a reduction in knowledge spillovers among firms that otherwise would lead to higher innovative performance on the aggregate level (Marx, Singh, & Fleming, 2015;Saxenian, 1996). Our findings further aggravate these concerns as our results indicate that inventor mobility and alliance formation are complements.…”
Section: Effects Of Inventor Mobilitymentioning
confidence: 99%